2010
DOI: 10.1016/j.molcel.2009.12.036
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-Mediated Cleavage, IAP Binding, and Ubiquitination: Linking Three Mechanisms Crucial for Drosophila NF-κB Signaling

Abstract: Innate immune responses are critical for the immediate protection against microbial infection. In Drosophila, infection leads to the rapid and robust production of antimicrobial peptides, through two NF-κB signaling pathways - IMD and Toll. The IMD pathway is triggered by DAP-type peptidoglycan, common to most Gram-negative bacteria. Signaling downstream from the peptidoglycan receptors is thought to involve K63-ubiquitination and caspase-mediated cleavage, but the molecular mechanisms remain obscure. We now s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
180
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 148 publications
(188 citation statements)
references
References 44 publications
6
180
0
2
Order By: Relevance
“…diap2 mutant flies fail to activate NF-kB-mediated expression of antibacterial peptide genes and, consequently, rapidly succumb to bacterial infection (Leulier et al 2006a;Huh et al 2007). DIAP2-mediated signaling to NF-kB critically depends on its Ub-E3 ligase activity (Leulier et al 2006a;Huh et al 2007;Paquette et al 2010;Meinander et al 2012). In conjunction with the E2 Ub-conjugating enzymes Effete (UBC5) and UEV1a/ Bendless (UEV1a/Ubc13) (Zhou et al 2005;Paquette et al 2010), DIAP2 promotes the conjugation of K63-linked Ub chains on IMD and DREDD (also referred to as DCP-2) (Paquette et al 2010;Meinander et al 2012), the Drosophila ortholog of caspase-8.…”
Section: Iap-mediated Regulation Of Innate Immunity and Cell Survivalmentioning
confidence: 99%
See 2 more Smart Citations
“…diap2 mutant flies fail to activate NF-kB-mediated expression of antibacterial peptide genes and, consequently, rapidly succumb to bacterial infection (Leulier et al 2006a;Huh et al 2007). DIAP2-mediated signaling to NF-kB critically depends on its Ub-E3 ligase activity (Leulier et al 2006a;Huh et al 2007;Paquette et al 2010;Meinander et al 2012). In conjunction with the E2 Ub-conjugating enzymes Effete (UBC5) and UEV1a/ Bendless (UEV1a/Ubc13) (Zhou et al 2005;Paquette et al 2010), DIAP2 promotes the conjugation of K63-linked Ub chains on IMD and DREDD (also referred to as DCP-2) (Paquette et al 2010;Meinander et al 2012), the Drosophila ortholog of caspase-8.…”
Section: Iap-mediated Regulation Of Innate Immunity and Cell Survivalmentioning
confidence: 99%
“…Recruitment of DIAP2 targets DREDD for K63-linked ubiquitylation, which allows Ub-mediated aggregation and activation of DREDD (Meinander et al 2012). Active DREDD subsequently cleaves IMD (Paquette et al 2010). Upon cleavage, IMD exposes an IBM at its neo-NH 2 terminus, which binds to the BIR2/3 of DIAP2.…”
Section: Iap-mediated Regulation Of Innate Immunity and Cell Survivalmentioning
confidence: 99%
See 1 more Smart Citation
“…We have shown that the cleavage and subsequent ubiquitination of the imd protein are crucial events during signaling (16). Because YopJ was proposed to act as a ubiquitin-protein protease (7,8), we examined whether either of these IMD modifications were altered in stable cell lines expressing YopJ.…”
Section: Resultsmentioning
confidence: 99%
“…Cleaved-IMD is then K63-polyubiquitinated through its association with the E3 ligase DIAP2 (16). These K63-polyubiquitin chains are proposed to then recruit and activate the downstream MAP3 kinase dTAK1, as reported for mammalian NF-κB signaling pathways (17,18).…”
Section: Drosophila Immunity | Innate Immunitymentioning
confidence: 89%